The effect of ease of use of M-Pajak and ease of use of e-form on MSMEs taxpayer compliance - Tengku Eka Susilawaty; An Suci Azzahra (Institute of Computer Science (IOCS), 2023)
When a taxpayer complies with all of his or her tax obligations and uses all of their tax privileges, this is known as taxpayer compliance. Tax revenue increases with better taxpayer compliance; conversely, when taxpayer compliance is low, tax revenue and state treasury both decline. As a result, DJP introduced the M-Pajak application and E-Form system, one of the tax administration reforms, with the goal of facilitating taxpayer access to more individualized, quicker, and MSMEs-friendly income tax reporting. The purpose of this study is to determine whether MSMEs taxpayer compliance in Pematang Serai Village, Langkat Regency, North Sumatra, is influenced by how simple M-Pajak and E-Form are to use. 35 MSME taxpayers made up the sample. The research methodology is quantitative, and descriptive statistics with multiple linear regression techniques are used for data analysis. According to the study's findings, M-Pajak and E-Form accessibility both partially and concurrently influence taxpayer compliance.This demonstrates that the simpler a DJP application or system is to use, the higher the rate of taxpayer compliance will be because it's simpler for taxpayers to comply with their tax responsibilities.